2021
DOI: 10.1088/1674-1056/ac11ea
|View full text |Cite
|
Sign up to set email alerts
|

Barrier or easy-flow channel: The role of grain boundary acting on vortex motion in type-II superconductors*

Abstract: Grain boundaries (GBs), as extremely anisotropic pinning defects, have a strong impact on vortex motion in type-II superconductors, and further on the macro level dominates the superconductivity for example the critical current density. Many previous studies indicated that mostly GB plays the role of a strong barrier for vortex motion, while an easy-flow channel just under some certain conditions. In order to thoroughly make clear of the questions of what is exactly the role of GB on vortex motion and how it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The geometric structure we simulate is an infinite superconducting slab containing the GB networks with random angles, which belongs to the category of two-dimensional (2D) periodic system. According to previous researches, [26] the GBs are modelled as the potential wells, because the behavior of the vortices in the vicinity of the GB is similar to the motion of charge carriers caused by the electric field. We assume that the GB is composed of a series of dislocations (red dots) distributed along the GB and the local electric fields applied to the specific areas, normal to the direction of the GB as shown in Fig.…”
Section: Model For Vortex Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The geometric structure we simulate is an infinite superconducting slab containing the GB networks with random angles, which belongs to the category of two-dimensional (2D) periodic system. According to previous researches, [26] the GBs are modelled as the potential wells, because the behavior of the vortices in the vicinity of the GB is similar to the motion of charge carriers caused by the electric field. We assume that the GB is composed of a series of dislocations (red dots) distributed along the GB and the local electric fields applied to the specific areas, normal to the direction of the GB as shown in Fig.…”
Section: Model For Vortex Dynamicsmentioning
confidence: 99%
“…The related parameters E (the electric field intensity) and q (charge of the vortices) are tunable parameters. The pinning potential of the special pins along the GB is determined by [26] U vs (r…”
Section: Model For Vortex Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, for a system with small size, it was found that the critical current density is not sensitive to grain size until the grain size is sufficiently small in polycrystalline superconductors [37], which is not consistent with experiments of Nb 3 Sn. It was also found that GBs not only acts as the pinning centers for vortices, but also provides an easy-flow channel for vortex motion [38,39], which depends on the GB angle [40][41][42]. However, the previous theoretical works mainly focus on one GB or very small amount of GBs.…”
Section: Introductionmentioning
confidence: 99%